Classroom assessment : - Airasian, Peter W. (McGraw-Hill, 2005)
Classroom Assessment: Concepts and Applications views classroom assessment as an everyday, ongoing, integral part of teaching, not something that is separated from life in classrooms. The text is thus organized in a manner that follows the natural progression of teacher decision making, from organizing the class as a learning community to planning and conducting instruction to the formal evaluation of learning and, finally, to grading. Classroom Assessment presents complex concepts clearly so that pre-service teachers can understand them, and solidly grounds these concepts in best practice through practical, real, well-integrated examples. The text conceives of classroom assessment in a broader way than many other texts. It focuses not only on the assessment needs of testing, grading, interpreting standardized tests, and performance assessments but also on assessment concerns in organizing a classroom at the start of school, planning and implementing instruction, and strategies of teacher self reflection.